2017
DOI: 10.1111/cei.12993
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA ameliorates chronic arthritis in mice by modulating neutrophil activities

Abstract: Rheumatoid arthritis (RA) is a chronic immune inflammatory disease mediated by the influx of immune cells into the synovial joint space. As Tanshinone IIA (TIIA) has potent anti-oxidant and anti-inflammatory activities, we used the adjuvant-induced arthritis (AA) murine model of RA to investigate the impact of TIIA on RA and immune cell activation. The anti-arthritic activity of TIIA was investigated in an adjuvant-induced arthritis model of RA in mice. Myeloperoxidase and neutrophil elastase expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Tanshinone IIA, a terpene extracted from Salvia miltiorrhiza, inhibits neutrophil activation, infiltration and apoptosis, leading to decreased MPO release. In agreement with these findings, another study found reduced tissue damage and joint inflammation in an adjuvantinduced arthritis model (Zhang et al, 2017).…”
Section: Modulation Of Signaling Pathways Associated With Inflammatorsupporting
confidence: 64%
See 1 more Smart Citation
“…Tanshinone IIA, a terpene extracted from Salvia miltiorrhiza, inhibits neutrophil activation, infiltration and apoptosis, leading to decreased MPO release. In agreement with these findings, another study found reduced tissue damage and joint inflammation in an adjuvantinduced arthritis model (Zhang et al, 2017).…”
Section: Modulation Of Signaling Pathways Associated With Inflammatorsupporting
confidence: 64%
“…In this context, alterations in the inflammatory mediator's cascades play a pivotal role in the pathophysiological processes underlying inflammation and tissue destruction in arthritic diseases. Some studies indicate that the beneficial pharmacological properties of terpenes against arthritis phenomena are related to modulation of several intracellular signaling pathway proteins, such as RANKL (Wang et al, 2016), NFκB (Z. M. , the MAPK family (Chen et al, 2015), COX-2 (Lee et al, 2015), iNOS (Lee et al, 2015, PGE-2 (Li et al, 2009), matrix metalloproteinases (Liu et al, 2015, Nanjundaiah et al, 2012, MPO (Zhang et al, 2017) and c-FOS (Kang et al, 2008). Terpenes can provoke the activation or inhibition of these molecules or pathways reducing the diseases progression.…”
Section: Modulation Of Signaling Pathways Associated With Inflammatormentioning
confidence: 99%
“…Neutrophils are the most abundant type of white blood cells, activation of which is a key feature of inflammatory diseases (Hwang et al, ). Triptolide, tanshinone IIA, isopedicin, viscolin, and luteolin inhibit the inflammatory activities of neutrophils to ameliorate RA (Huang et al, ; Hwang et al, ; Hwang, Leu, Kao, Tang, & Chang, ; Yang et al, ; Zhang et al, ). Infiltration of the synovium by mononuclear cells (monocytes and lymphocytes) is one of the main features of RA (Liote, Boval‐Boizard, Weill, Kuntz, & Wautier, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%
“…The joint morphology shows that sinomenine suppresses synovial hypertrophied and cartilage destruction (Mu et al, ). Through histopathological examination, tanshinone IIA, artemether, tripterine, (−)‐epicatechin‐3‐ O ‐β‐ d ‐allopyranoside, shikonin, daphnetin, and kinsenoside can effectively ameliorate the bone and cartilage destruction in the joints of RA model (Cuzzocrea et al, ; Dai, Wang, & Zhang, ; Gao et al, ; Hsiao et al, ; Hsiao et al, ; Li, Zhang, et al, ; Zhang, Huang, et al, ). With the help of a dental X‐ray machine, researchers observe that sinomenine alleviates osteoporosis and cartilage or bone erosion in joint of RA rat model (Mu et al, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%
“…Due to its diverse pharmacologic properties, is categorized as one of the main commercial herbs in this country. In line, pharmacological research's indicate that diterpenoidic like compounds such as TIIA and CRY from Danshen exhibited remarkable properties for the treatment of cardiovascular [11,12,13,14], cerebrovascular [15,16], inflammatory diseases [17,18] and cancer [19,20,21].…”
Section: Introductionmentioning
confidence: 99%